Quantitative ultrasonic imaging of weave structure in textile composites - Yang, Xiaoyu (2024)
Textile composites owe their desirable mechanical properties to the intricate fabric architecture. However, manufacturing deviations can influence these attributes, significantly affecting their mechanical performance. Thus, ensuring the quality and structural integrity of fabric architectures has become pivotal, leading to the advancement of ultrasonic non-destructive testing techniques. However, existing techniques, primarily tailored for unidirectional laminates, often struggle with weave pattern extraction, given the complex features of fabric laminates. To address this gap, a pulse-echo ultrasound coupled to a 2D analytic-signal analysis is proposed. The 2D analytic-signal methodology autonomously discerns the complex ultrasound features from fabric laminates, streamlining weave pattern analysis. The study showcases ply-by-ply reconstruction of local weave patterns of fabric laminates with nominal layups of [#(0/90)]8 and [#(+45/−45)#(0/90)]5s, respectively. The efficacy of the methodology is ascertained through quantitative metrics, highlighting its innovative potential for through-depth extraction of local weave patterns in a swift and automated manner.